The Doctoral Research Abstracts: determinants of digital reference services acceptance in Malaysian research universities / Zubaidah Iberahim - Iberahim, Zubaidah (Institute of Graduate Studies, UiTM, 2018)
At the current rate of development, many people are concerned about gaining access to information in the virtual arena. Therefore, most libraries have taken the effort to make use of the Internet and have tried to establish an effective presence of the virtual aspect. Considering the extensive impact of technology upon changing the way library and user to communicate, it is worthwhile to study and to comprehend the acceptance of Digital Reference Services (DRS). In fact, numerous academic libraries in developing countries at present are greatly concerned about Information Communication Technology (ICT) use and acceptance. Therefore, this study is one of the very few attempts that examine the influential factors, as well as predict the acceptance and the use of DRS among Malaysian Research University (RU) libraries. Hence, the key objective is to identify the antecedents of DRS acceptance. In this study, ten factors have been listed as strong empirical evidence that successfully predicted the acceptance and use of DRS, which have been categorized into four groups: technology factors, organizational factors, social factor, and task factors. Moreover, the model identifies the structural relationships between the constructs, which were examined via Structural Equation Modeling (SEM) with Analysis of Moment Structures (AMOS)…